2019
DOI: 10.17344/acsi.2018.4719
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Five-Membered Heterocycles and Their Activity against Candida Yeasts

Abstract: Some new tetrazole derivatives were prepared by the reaction between the prepared azomethine compounds I 6-I 10 with sodium azide in anhydrous tetrahydrofuran (THF) with a few drops of distilled water and under reflux conditions. Azomethine compounds were prepared by thermal condensation reactions of aromatic aldehydes with primary aromatic amines. The prepared compounds (tetrazole derivatives) were screened for their antibacterial activity (by disc diffusion method). Compound I 6 is the most active derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…General procedure for prepare of imine compounds [5][6][7][8]: Imine compounds are preparation by mixing 0.01moleof amine and 0.02 mole ofaldehydepresence trace of glacial acetic acid in 25 mL abs. ethanol, the reaction completed for 4hours, the purity of the Imine compounds were monitored with Thin Lear Chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…General procedure for prepare of imine compounds [5][6][7][8]: Imine compounds are preparation by mixing 0.01moleof amine and 0.02 mole ofaldehydepresence trace of glacial acetic acid in 25 mL abs. ethanol, the reaction completed for 4hours, the purity of the Imine compounds were monitored with Thin Lear Chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition zone of 100% was less than the inhibition zone of 80%. This is due to the fact that the high concentration of 100% prevents the spread of the lactozepine well [33]. Antioxidant activity of the synthesise compound was also assessed in order to examine the ability of the compound to scavenge the free radicals using the DPPH reagent in a free radical scavenging assay.…”
Section: Biological and Antioxidant Activity Of Lactozepinementioning
confidence: 99%
“…On the other hand, hydrazones (iNHN=C‐1) are known as biologically active fragements, which are widely used as a scaffold in agricultural chemistry . It has been reported that derivatives of hydrazones are shown to possess a wide range of biological activities, such as antifungal, antibacterial, insecticidal, herbicidal, antiviral and anticancer activities . Heretofore, some pharmaceutical companies have developed dozens of fungicides, insecticides, plant growth regulators such as benquinox, hydramethylnon and diflufenzopyr .…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] It has been reported that derivatives of hydrazones are shown to possess a wide range of biological activities, such as antifungal, antibacterial, insecticidal, herbicidal, antiviral and anticancer activities. [34][35][36][37][38][39] Heretofore, some pharmaceutical companies have developed dozens of fungicides, insecticides, plant growth regulators such as benquinox, hydramethylnon and diflufenzopyr. [40][41][42] All of the findings inspired us to design the bioactive structures with these functional motifs as potential agrochemical leads for plant disease control.…”
mentioning
confidence: 99%